2021
DOI: 10.1021/acs.nanolett.1c01100
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Control of Charge Doping in n-Type Topological Insulators

Abstract: Spatially controlling the Fermi level of topological insulators and keeping their electronic states stable are indispensable processes to put this material into practical use for semiconductor spintronics devices. So far, however, such a method has not been established yet. Here we show a novel method for doping a hole into n-type topological insulators Bi 2 X 3 (X= Se, Te) that overcomes the shortcomings of the previous reported methods. The key of this doping is to adsorb H 2 O on Bi 2 X 3 decorated with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Exposure to ambient environments has been shown to alter measured ARPES spectra and the surface composition in Bi 2 Se 3 [31][32][33][34]. The topological surfaces states can be modified by forming 2D quantum well states in ambient conditions [32], and can present band-bending and controlled charge-doping after dosing H 2 O [31] and UV irradiation [35]. In most cases, the robust topological surface states are still present in Bi 2 Se 3 despite air exposure and oxidation [32,36].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ambient environments has been shown to alter measured ARPES spectra and the surface composition in Bi 2 Se 3 [31][32][33][34]. The topological surfaces states can be modified by forming 2D quantum well states in ambient conditions [32], and can present band-bending and controlled charge-doping after dosing H 2 O [31] and UV irradiation [35]. In most cases, the robust topological surface states are still present in Bi 2 Se 3 despite air exposure and oxidation [32,36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the role of the surface atomic structure in TSSs is regarded as rather unimportant because of the robustness. Some theoretical and experimental studies reported modification of TSSs by surface treatments, such as surface oxidization 4 , chemical or photochemical ageing 5 , 6 , and a small interlayer rotation forming a moiré modulation on the surface 7 . However, such previous works were focused on how to perturb the pristine TSS.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the role of the surface atomic structure in TSSs is regarded as rather unimportant because of the robustness. Some theoretical and experimental studies reported modification of TSSs by surface treatments, such as surface oxidization [4], chemical or photochemical ageing [5,6], and a small interlayer rotation forming a moiré modulation on the surface [7]. However, such previous works were focused on how to perturb the pristine TSS.…”
mentioning
confidence: 99%